Pulselessness After Initiation of Cardiopulmonary Resuscitation for Bradycardia in Hospitalized Children: Prevalence, Predictors of Survival, and Implications for Hospital Profiling. Issue 5 (30th July 2019) - Khera, Rohan; Tang, Yuanyuan; Girotra, Saket; Nadkarni, Vinay M.; Link, Mark S.; Raymond, Tia T.; Guerguerian, Anne-Marie; Berg, Robert A.; Chan, Paul S.
Abstract : Background: Cardiopulmonary resuscitation (CPR) is initiated in hospitalized children with bradycardia and poor perfusion. However, their rate of progression to pulseless cardiac arrest despite CPR and the differences in survival compared with initially pulseless arrest are unknown. We examined the prevalence and predictors of survival of children who progress from bradycardia to pulseless in-hospital cardiac arrest despite CPR. Methods: Pediatric patients >30 days and <18 years of age who received CPR at hospitals participating in Get With The Guidelines–Resuscitation during 2000 to 2016 were included. Each CPR event was classified as bradycardia with pulse, bradycardia with subsequent pulselessness, and initial pulseless cardiac arrest. We assessed risk-adjusted rates of survival to hospital discharge using multilevel Poisson regression models. Results: Overall, 5592 pediatric patients were treated with CPR, of whom 2799 (50.1%) received CPR for bradycardia with poor perfusion and 2793 (49.9%) for initial pulseless cardiac arrest. Among those with bradycardia, 869 (31.0%, or 15.5% of cohort) became pulseless after a median of 3 minutes of CPR (interquartile range, 1–9 minutes). Rates of survival to discharge were 70.0% (1351 of 1930) for bradycardia with pulse, 30.1% (262 of 869) for bradycardia progressing to pulselessness, and 37.5% (1046 of 2793) for initial pulseless cardiac arrest ( P for difference across groups <0.001). Children who became pulseless despite CPR for bradycardia had a 19% lower likelihood (risk ratio, 0.81 [95% CI, 0.70, 0.93]; P =0.004) of surviving to hospital discharge than those who were initially pulseless. Among children who progressed to pulselessness despite CPR for bradycardia, a longer interval between CPR and pulselessness was a predictor of lower survival (reference, <2 minutes; for 2–5 minutes, risk ratio, 0.54 [95% CI, 0.41–0.70]; for >5 minutes, risk ratio, 0.41 [95% CI, 0.32–0.53]). Conclusions: Among hospitalized children in whom CPR is initiated, half have bradycardia with poor perfusion at the initiation of chest compressions, and nearly one-third of these progress to pulseless in-hospital cardiac arrest despite CPR. Survival was significantly lower for children who progress to pulselessness despite CPR compared with those who were initially pulseless. These findings suggest that pediatric patients who lose their pulse despite resuscitation attempts are at particularly high risk and require a renewed focus on postresuscitation care. Abstract : Supplemental Digital Content is available in the text.